2018
DOI: 10.1177/155892501801300101
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Calixarene-PI Nanofibers and Application as a Selective Adsorbent for Heavy Metal Ions

Abstract: In order to utilize the adsorption selectivity of calixarenes towards heavy metal ions, calixarene functionalized polyimide (Calix-PI) fibers were prepared by three main synthesis procedures including preparation of the calixarene polyamide acid (Calix-PAA) spinning solution via amidation, fabrication of the Calix-PAA fibers by electrospinning, and preparation of the Calix-PI fibers via thermal imidization on the Calix-PAA fibers. The Calix-PI fibers were characterized by Fourier transform infrared spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The 13 CNMR spectrum of BN22E@DMSO-d 6 shows a total of ten signals while that of BN22M@DMSO-d 6 shows a total of eight signals. In the 13 CNMR spectrum of BN22E, there are two pairs of signals at 120.75 ppm, 120.82 ppm and 153.20 ppm and 153.35 ppm. In BN22M however, for each pair of signals observed in BN22E there is a single peak at 120.60 ppm and 153.38 ppm respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 13 CNMR spectrum of BN22E@DMSO-d 6 shows a total of ten signals while that of BN22M@DMSO-d 6 shows a total of eight signals. In the 13 CNMR spectrum of BN22E, there are two pairs of signals at 120.75 ppm, 120.82 ppm and 153.20 ppm and 153.35 ppm. In BN22M however, for each pair of signals observed in BN22E there is a single peak at 120.60 ppm and 153.38 ppm respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Calixarenes and their derivatives have of late been subject of applications ranging from sensing to electronics; this driven by the fact that these molecules are capable of acting as selective receptors for both metal ions and organic compounds 6 . To this end, there have been several reports for which calixarenes and their derivatives have been used for selective adsorption of metal ions [11][12][13] , separation of organic mixtures and solutions 4,14-16 and sensing 17,18 . In an attempt to obtain better performing adsorbents, calixarene have either been made into thin films 4,16 or supported on materials such as resins 12 for eventual wetting studies and adsorption of several compounds.…”
Section: Introductionmentioning
confidence: 99%
“…It has the characteristics of artificial cavity adjustment, variable conformation, easy chemical modification and modification, and stable properties [4]. It is often used for heavy metal ion coordination and the research object of the adsorbent [5]. Some studies found that the coordination cavity of all-hydroxycalix [4] arene is similar to the cavity structure required for cadmium ion complexes [6].…”
Section: Introductionmentioning
confidence: 99%